2013
DOI: 10.1186/1756-3305-6-192
|View full text |Cite
|
Sign up to set email alerts
|

Bendiocarb resistance in Anopheles gambiae s.l. populations from Atacora department in Benin, West Africa: a threat for malaria vector control

Abstract: BackgroundOwing to pyrethroid resistance in An. gambiae, the carbamate and organophosphate insecticides are currently regarded as alternatives or supplements to pyrethroids for use on mosquito net treatments. Resistance monitoring is therefore essential to investigate the susceptibility of An. gambiae s.l to these alternative products.MethodsTwo to three day old adult female Anopheles mosquitoes were reared from larvae collected in the five districts (Kouandé, Natitingou, Matéri, Péhunco, Tanguiéta) of the Ata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
70
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 29 publications
(31 reference statements)
14
70
0
5
Order By: Relevance
“…The twenty-five females of An. gambiae were introduced into each tube and monitored at different time intervals (10,15,20,30,45, 60 minutes), the number "knocked-down" were recorded. After one hour exposure, mosquitoes were transferred into holding tubes and provided with cotton wool soaked with a 10% honey solution.…”
Section: Insecticide Susceptibility Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…The twenty-five females of An. gambiae were introduced into each tube and monitored at different time intervals (10,15,20,30,45, 60 minutes), the number "knocked-down" were recorded. After one hour exposure, mosquitoes were transferred into holding tubes and provided with cotton wool soaked with a 10% honey solution.…”
Section: Insecticide Susceptibility Testsmentioning
confidence: 99%
“…More recently in Benin, several studies pointed out An. gambiae resistance to bendiocarb [20,21] and showed that the mean Ace-1 mutation frequency had increased significantly from 2010 to 2012 after two years of IRS campaign using bendiocarb in Atacora region in the northern part of the country [22,23]. However, these studies cleary showed the evidence of bendiocarb resistance in An.…”
Section: Introductionmentioning
confidence: 99%
“…Different vector control strategies are currently employed, for example indoor residual spraying (IRS) or insecticide-treated plastic sheeting, but the use of insecticide-treated nets (ITNs) is so far the most efficient and used strategy to reduce malaria transmission and morbidity by decreasing human-vector contact. However, parasite resistance to antimalarial treatment [2] and mosquito vector resistance to insecticides [3,4] seriously impair the success of malaria control measures.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that exposure to parasites and their encoded antigens can induce a degree of clinical immunity and provide the rationale and incentive for pursuing the development of anti-parasitic vaccines. Furthermore, while the advent of novel anti-parasitic drugs have successfully led to a decrease in the incidence rates of parasitic infections, they have also aided in positively selecting for both resistant parasites and their vectors [4, 5]. Thus, alternative immune-based approaches and effective vaccines against Plasmodium and other protozoan and helminth parasites are desperately needed.…”
Section: Introductionmentioning
confidence: 99%